2021
DOI: 10.3390/cancers13235939
|View full text |Cite|
|
Sign up to set email alerts
|

GSK-3 Inhibition Is Cytotoxic in Glioma Stem Cells through Centrosome Destabilization and Enhances the Effect of Radiotherapy in Orthotopic Models

Abstract: Background: Previous data on glycogen synthase kinase 3 (GSK-3) inhibition in cancer models support a cytotoxic effect with selectivity for tumor cells compared to normal tissue but the effect of these inhibitors in glioma has not been widely studied. Here, we investigate their potential as cytotoxics in glioma. Methods: We assessed the effect of pharmacologic GSK-3 inhibition on established (U87, U251) and patient-derived (GBM1, GBM4) glioblastoma (GBM) cell lines using cytotoxicity assays as well as undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These results suggest a higher percentage of dead cells after CHIR99021 treatment, with the increase in the S-phase possibly indicating cell cycle arrest at this phase. In line with this, various studies have reported alterations in cell cycle distribution after GSK-3 inhibition in GBM cell lines and patient-derived GBM cultures (Acikgoz et al 2019;Brüning-richardson et al 2021). With regard to circadian disruption, propidium iodide-stained cells revealed accumulation in the S-phase in the Per2 KD condition after serum stimulation with respect to control cultures.…”
Section: Discussionmentioning
confidence: 57%
“…These results suggest a higher percentage of dead cells after CHIR99021 treatment, with the increase in the S-phase possibly indicating cell cycle arrest at this phase. In line with this, various studies have reported alterations in cell cycle distribution after GSK-3 inhibition in GBM cell lines and patient-derived GBM cultures (Acikgoz et al 2019;Brüning-richardson et al 2021). With regard to circadian disruption, propidium iodide-stained cells revealed accumulation in the S-phase in the Per2 KD condition after serum stimulation with respect to control cultures.…”
Section: Discussionmentioning
confidence: 57%
“…These results suggest a higher percentage of dead cells after CHIR99021 treatment, with the increase in the S-phase possibly indicating cell cycle arrest at this phase. In line with this, various studies have reported alterations in cell cycle distribution after GSK-3 inhibition in GBM cell lines and patient-derived GBM cultures [43, 44]. With regard to circadian disruption, propidium iodide-stained cells revealed accumulation in the S-phase in the Per 2 KD condition after serum stimulation with respect to control cultures.…”
Section: Discussionmentioning
confidence: 57%
“…Dose-response curves using the selective inhibitors of CK1 ε/δ (PF670462), GSK-3 (CHIR99021), and CRY degradation (KL001) showed IC50 in the low micromolar range after 48 h of treatment. Although different GSK-3 inhibitors have been evaluated in GBM models [27,[43][44][45][46][47][48], our results demonstrate for the first time that CHIR99021 treatment impairs GBM cell viability. The migratory capacity of tumor cells is a characteristic of more aggressive or malignant cancer types.…”
Section: Discussionmentioning
confidence: 68%
“…The selective pharmacological inhibition of GSK-3 by CHIR99021 has also been shown to impair cell proliferation in epithelioid sarcoma (Russi et al 2021 ) and non-small cell lung carcinoma (O’flaherty et al 2019 ). Although different GSK-3 inhibitors have been evaluated in GBM models (Kotliarova et al 2008 ; Korur et al 2009 ; Miyashita et al 2009 ; Furuta et al 2017 ; Acikgoz et al 2019 ; Kitabayashi et al 2019 ; Brüning‐richardson et al 2021 ), our results demonstrate for the first time that CHIR99021 treatment impairs GBM cell viability. The migratory capacity of tumor cells is a characteristic of more aggressive or malignant cancer types.…”
Section: Discussionmentioning
confidence: 60%